Burn : a novel - Howard, Linda, 1950- (Ballantine Books, 2009)
When Jenner Redwine wins the lottery, she never imagined how much it would cost her. Luckily she finds an ally-and a guide to the rarefied realm of privilege in a shy, kind-hearted heiress who invites Jenner on a charity cruise. But what should have been a "Love Boat" cruise suddenly turns into a game of dizzying intrigue and harrowing danger, and Jenner finds herself taken hostage by a menacing stranger--a stranger that helps her rediscover feelings she hasn't had in years. Now if she can only survive to live a life worth living ....